Letter (copy) : Foodstuffs for Spain - Tewson, Vincent
029-0149-001 HVT/EK/980. Secretary's. 28th May, 1937. Sra. Carmen de Cossio, Spanish Women's Committee For Help to Spain, 22, Taunton Avenue, London, S.W.20. Dear Madam, FOODSTUFFS FOR SPAIN. Since receiving your letter of the 13th May I have attempted on two occasions to make contact with you by telephone but have not been successful. I should be glad if you could arrange to come to this office on Monday next, 31st May, at 2.30 p.m. in order that we might talk over the suggestion contained in your letter. Yours faithfully, Assistant Secretary. 292/946/29/149